Evaluation and Comparison of Serological Methods for COVID-19 Diagnosis - Gong, Fanwu; Wei, Hua-xing; Li, Qiangsheng; Liu, Liu; Li, Bofeng (Frontiers in Molecular Biosciences, 2021)
The worldwide pandemic of COVID-19 has become a global public health crisis. Various clinical diagnosis methods had been developed to distinguish COVID-19 infected patients from healthy people. Nucleic acid test, as a golden standard for virus detection, is suitable for early diagnosis. However, due to low amount of viral nucleic acid in respiratory tract, the sensitivity of nucleic acid detection is unsatisfactory. As a result, serological screening began to be widely used with merits of simple procedures, lower cost and shorter detection time. Serological tests currently include enzyme-linked immunosorbent assay (ELISA), lateral flow immunoassay (LFIA) and chemiluminescence immunoassay (CLIA), etc. This review describes various serological methods, discusses the performance and diagnostic effects of different methods, points out the problems and the direction of optimization, to improve the efficiency of clinical diagnosis. These increasingly sophisticated and diverse serological diagnostic technologies will help human beings to control the spread of COVID-19.